PENGARUH INCOME SMOOTHING, GOOD COORPORATE GOVERNANCE, PERSENTASE KEPEMILIKAN MANAJERIAL DAN FIRM SIZE TERHADAP TINGKAT PENGUNGKAPAN LAPORAN KEUANGAN - Deranika Ratna Kristiana (Jurnal Akuntansi, 2016)
This research aims to examine the effect of Income Smoothing to the level of disclosure of financial reports. The implementation of good corporate governance effects to the level of disclosure of financial reports, managerial ownership effects the to the level of disclosure of financial reports and firm size effects to the level of disclosure of financial reports. The sample used in this research is the top 10 company CGPI (Corporate Governance Perception Index) in the period from 2010 to 2014. Hypotheses are test by multiple linear regression. The results show that Income Smoothing is a positive influence on the level of disclosure of financial statement. There are positive effect between good corporate governance to the level of disclosure of financial reports. There is no positive correlation between percentage of managerial ownership to the level of disclosure of financial reports and positive influence of company size and the level of disclosure of financial statements. Keywords: financial statement disclosure, income smoothing, good corporate governance, managerial ownership, and firm size